2021
DOI: 10.1101/2021.02.03.428533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel capsid protein network allows the characteristic inner membrane structure of Marseilleviridae giant viruses

Abstract: Marseilleviridae is a family of the new order of giant viruses, which exhibit a characteristic inner membrane. Here, we investigated the entire structure of tokyovirus, a species of Marseillevirus at 7.7 Å resolution using 1 MV high-voltage cryo-EM and single particle analysis. The minor capsid lattice formed by five proteins, shows a novel structure compared to other icosahedral giant viruses. Under the minor capsid proteins, scaffold proteins connect two five-fold vertices and interact with the inner membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…As reported in other giant virus capsids (Chihara et al 2021, Fang et al 2019, Born et al, 2018, the five-fold axis of the Melbournevirus capsid is filled with a penton base protein pentamer. We performed a rigid body fit of the penton base protein from PBCV-1 (Fang et al, 2019) to this density, but the quality of the fit was marginal.…”
Section: The Penton Base Proteinsupporting
confidence: 60%
See 4 more Smart Citations
“…As reported in other giant virus capsids (Chihara et al 2021, Fang et al 2019, Born et al, 2018, the five-fold axis of the Melbournevirus capsid is filled with a penton base protein pentamer. We performed a rigid body fit of the penton base protein from PBCV-1 (Fang et al, 2019) to this density, but the quality of the fit was marginal.…”
Section: The Penton Base Proteinsupporting
confidence: 60%
“…3B, C). Previously, Okamoto et al reported that an uncharacterised protein, MEL_236, appeared to have the same abundance as the MCP protein (Okamoto et al, 2018 the correct size (given a margin of error for SDS-PAGE size determination) to correspond with the PAS stain-sensitive kDa protein of tokyovirus previously reported (Chihara et al, 2021).…”
Section: The Major Capsid Proteinmentioning
confidence: 93%
See 3 more Smart Citations